If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (Y + -3)(3y + -4) = 0 Reorder the terms: (-3 + Y)(3y + -4) = 0 Reorder the terms: (-3 + Y)(-4 + 3y) = 0 Multiply (-3 + Y) * (-4 + 3y) (-3(-4 + 3y) + Y(-4 + 3y)) = 0 ((-4 * -3 + 3y * -3) + Y(-4 + 3y)) = 0 ((12 + -9y) + Y(-4 + 3y)) = 0 (12 + -9y + (-4 * Y + 3y * Y)) = 0 (12 + -9y + (-4Y + 3yY)) = 0 Reorder the terms: (12 + -4Y + -9y + 3yY) = 0 (12 + -4Y + -9y + 3yY) = 0 Solving 12 + -4Y + -9y + 3yY = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -4Y + -9y + -12 + 3yY = 0 + -12 Reorder the terms: 12 + -12 + -4Y + -9y + 3yY = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -4Y + -9y + 3yY = 0 + -12 -4Y + -9y + 3yY = 0 + -12 Combine like terms: 0 + -12 = -12 -4Y + -9y + 3yY = -12 Add '9y' to each side of the equation. -4Y + -9y + 9y + 3yY = -12 + 9y Combine like terms: -9y + 9y = 0 -4Y + 0 + 3yY = -12 + 9y -4Y + 3yY = -12 + 9y Reorder the terms: 12 + -4Y + -9y + 3yY = -12 + 9y + 12 + -9y Reorder the terms: 12 + -4Y + -9y + 3yY = -12 + 12 + 9y + -9y Combine like terms: -12 + 12 = 0 12 + -4Y + -9y + 3yY = 0 + 9y + -9y 12 + -4Y + -9y + 3yY = 9y + -9y Combine like terms: 9y + -9y = 0 12 + -4Y + -9y + 3yY = 0 The solution to this equation could not be determined.
| 3x^2-2x^2= | | t^2+10t=-4 | | 1/2x2=b | | -32*x*x+120*120*x-80*120*120=0 | | 28(28+28)=1680 | | 6a^2+30= | | 3m-10= | | x^3+9x^2-4x-36=0 | | x-10+x+2=180 | | A=(2-n)180 | | 3.8+5.2-6.7=11.3 | | 45=9(x-5) | | 8xb=5 | | -2r=2 | | 4p-2c+2p=8c | | 36t^2+162t+16=0 | | -5p=-20 | | 6xb=3 | | (x-80)(7x+5)=0 | | 3x^2+3y^2-24x+12y-15=0 | | 4x+3y-9(6x-5y)= | | M+8=2(2m+2)+m | | 8x^2-2x-3=y | | 1/6(3/4x-2)=1/5 | | 2/3p=9/4-3/8 | | -5t^2+20t+15=3t+3 | | 21X^6-48x^2-1/3x^2 | | -5x+3x^2=12 | | 0=x^2+35x-750 | | 10+0.10s=0+0.35s | | x^2-142=0 | | P^2/4-3=33 |